Performance-based selection of sustainable construction solutions for external walls - Veludo, S.; Rato, V. (Global dwelling: Approaches to sustainability, design and participation, 2020)
This research is focused on the integration of sustainability and functional performance in architecture. While having an important contribution in terms of environmental impact, construction solutions also play a significant role in the reduction of energy use during the use phase of buildings. Therefore a careful, although simple, analysis of construction solutions integrating environmental and functional performance is needed to support the decision process in architectural design. A simplified methodology, using an environmental indicator and an energy-related functional indicator is implemented to assess how a set of construction solutions for external walls would perform in face of different objectives. The environmental indicator is obtained through the aggregation of the individual normalized values for the embodied energy and the carbon footprint. The functional indicator characterizes the energy performance of the wall, by aggregating the individual normalized values of the heat transfer coefficient and the net superficial thermal mass. These indicators are then integrated in a final weighted index to allow for a straightforward, yet effective understanding of the environmental impact of functional construction solutions. The set of construction solutions comprises different materials for cavity as well as single walls that are common in the building construction sector: ceramic brick masonries, reinforced concrete, mortar render and plasterboard as internal coating, synthetic or natural materials applied in two thicknesses for thermal insulation. Different combinations of these materials form the set of 90 heavyweight external walls that were calculated. Results show that it is possible to select construction solutions with a good environmental and functional performance. There is however a conflict between the objectives of reducing embodied environmental impact and increasing thermal inertia. This later may be an important comfort factor in the cooling season in residential architecture. The proposed methodology can be a comprehensive support tool to architects at the moment of selecting construction solutions, so that the principles of a sustainable construction are increasingly becoming a reality in architectural design.